A penny saved is a penny earned? Differences in male and female savings and consumption tradeoffs on online retail platforms. (January 2019) - Li, Meng; Patel, Pankaj C.; Wolfe, Marcus T.
Abstract: Online retailers in Asia are increasingly offering interest paying accounts to their users. Based on temporal discounting theory, however, customers might consider tradeoffs in opportunities to save money (offered yield by the online retailer × the account balance) versus withdrawing money from the account for online purchases. Based on a sample of 1.95 million transactions from 24, 591 customers, when short-term savings opportunities (7-day annualized yield × account balance) are greater, customers withdraw less money for purchase. Relative to females, males tend to withdraw less money for purchase from their account when long-term savings opportunities (1-year annualized yield × account balance) are higher. The findings have implications for temporal discounting behavior in online retail saving opportunities versus purchase transactions, and implications for online retailers who may cannibalize online sales by offering higher yields to online customers.